Auditing environmental governance for sustainable development: A content analysis of BPK’s performance audit reports in Indonesia - Anggraini, Putri; Alfian, Rakhmat (Badan Pemeriksa Keuangan Republik Indonesia, 2026)
Indonesia is aligning its National Medium-Term Development Plan (RPJMN) with the U.N.’s Sustainable Development Goals (SDGs) to address persistent environmental degradation. The Audit Board of the Republic of Indonesia (BPK) conducts performance audits to assess whether government programs allocate resources effectively to protect the environment. However, these reports remain underutilized in policy evaluation. This study reviews 139 BPK audit reports issued from 2015 to 2024 and identifies 1,526 findings, which collectively show that Indonesia continues to face major challenges in pursuing sustainable economic development. Recurring issues include inadequate water and sanitation infrastructure, slow progress in climate change mitigation, and weak enforcement of marine and land conservation. Through its audits, BPK evaluates program performance, highlights implementation gaps, and provides evidence-based recommendations intended to strengthen infrastructure development, law enforcement, community engagement, and broader sustainability initiatives. This study offers the first content analysis of BPK’s environmental performance audits, contributing to the sustainability literature in a developing-country context and supplying evidence-based insights for improving environmental governance. It further demonstrates how audit recommendations can guide policy reform and link audit findings to the SDGs.